KECERNAAN SERAT BUAH SAWIT (Palm Pressing Fibre) YANG DIFERMENTASI DENGAN JAMUR TIRAM (Pleurotus sp) VARIETAS FLORIDA - Basri, Moh (AgriSains, 2005)
The objective of the present work was to find out the effects of fermentation treatment using jamur tiram (Pleurotus sp.) on the stability of palm pressing fibre (PPF).  The digestibility (DDM, DOM, NDF, ADF) was measured in vitro after the method of Telley and Terry (1963).  Jamur tiram was grown on media having different composition of rice branch, CaCO3 and gibs [a) 16% + 2% + 2% ; b) 32% + 4% + 4% ; c) 48% + 6% + 6%]. The treatments to be studied were i) 100% PPF, ii) 80% PPF + jamur tiram on medium (a), iii) 6o% PPF + jamur tiram on medium (b), iv) 40% PPF + jamur tiram on medium (c).  The results indicated that treatment (ii) gave the highest digestibility followed by treatment (iii) and (iv).  Treatment (ii) also offered the best economic profit if compared to the rest. Key words : Digestibility, palm pressing fiber, jamur tiram.